'Red Storm Ahead': Securitisation of Energy in US–China Relations. (September 2014) - Nyman, Jonna
Energy is becoming more and more important to state survival and economic development, and is increasingly considered an issue of 'national security'. In 2005, the bid by China National Offshore Oil Corporation (CNOOC) for US energy company Unocal was securitised by US elite actors, who called for presidential action on the grounds of 'national security'. This article argues that securitisation of energy is problematic, as it impedes cooperation and encourages strategic and/or economic competition between states over energy supplies by tying energy to a national security 'us vs. them' scenario. Moreover, it limits the energy security debate. The article will use a securitisation approach to analyse the discourse of the Unocal affair, together with a smaller complementary case study of US–China cooperation on shale gas to show the possibility of dealing with energy in desecuritised terms. It argues that the current literature on energy 'security' analyses policy in overly simplistic competition/cooperation terms and fails to recognise the policy implications of securitising energy. In contrast, a securitisation approach to energy can explain the (re)presentation of energy as a policy issue and allows an analysis of how using particular discourse makes particular policy possible, while silencing alternative policy options. This has implications for policy-making in this area as energy policy/practice should be desecuritised.